A method and system for anti-corrosion and anti-wear based on high molecular polymer materials

By spraying the coating spray and conducting corrosion and wear resistance tests, the coating thickness is adjusted to meet specific environmental needs, and the corrosion and wear problems of polymer polymer materials during use are solved, achieving efficient and economical anti-corrosion and wear effects.

CN119331450BActive Publication Date: 2025-03-28INNER MONGOLIA MENGGANG ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411882234.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-28
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

Polymer polymer materials face the dual challenges of corrosion and wear during use, resulting in reduced performance and high maintenance costs. The existing anti-corrosion and wear-proof methods are costly and have insufficient anti-corrosion and wear-proof capabilities in different environments.

Method used

By preparing coating sprays, including adhesion coating sprays and resistant coating sprays, spraying them on the surface of polymer polymer materials, forming target polymer material groups, conducting corrosion and wear resistance tests, calculating anti-corrosion factors, and adjusting the coating thickness to meet the anti-corrosion and wear resistance requirements of specific environments.

Benefits of technology

It improves the anti-corrosion and wear resistance of polymer polymer materials, reduces the cost of anti-corrosion and wear resistance, and ensures that the performance of the material in different environments meets expectations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331450B_ABST
    Figure CN119331450B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of material corrosion and wear resistance, and is a method and system for corrosion and wear resistance based on high molecular polymer materials, comprising: obtaining an original polymer material group, spraying the original polymer material based on the original coating thickness to obtain a target polymer material group, performing corrosion treatment and friction treatment on the target polymer material group respectively to obtain a material corrosion resistance rate group and a material wear rate group, obtaining a corrosion resistance factor according to the material corrosion resistance rate group and the material wear rate group, judging whether the corrosion resistance factor is greater than a standard corrosion factor, if not, obtaining a target coating thickness according to a target thickness factor group, and if greater, recording the original coating thickness as an optimal coating thickness. The present invention improves the corrosion resistance and wear resistance of high molecular polymer materials and reduces the cost of corrosion resistance and wear resistance for high molecular polymer materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material anti-corrosion and anti-wear, and in particular to an anti-corrosion and anti-wear method and system based on high molecular polymer materials. Background Art

[0002] In modern industry and engineering, polymer materials are widely used in various environments and occasions due to their advantages such as light weight, corrosion resistance and good insulation performance. However, these polymer materials face the dual challenges of corrosion and wear during actual use, which not only limits the performance and service life of the materials, but may also lead to safety accidents and high maintenance costs. Therefore, it is particularly important to prevent corrosion and wear of polymer materials.

[0003] Currently, the corrosion and wear resistance of polymer materials is mainly achieved through composite materials. This method has the problem of high cost. In addition, due to the different corrosion and wear requirements of materials in different application environments, the corrosion and wear resistance of the polymer materials obtained by this method is relatively low in some environments. Summary of the invention

[0004] The present invention provides a method and system for preventing corrosion and wear based on high molecular polymer materials, the main purpose of which is to improve the anti-corrosion and anti-wear capabilities of high molecular polymer materials and reduce the cost of preventing corrosion and wear on high molecular polymer materials.

[0005] To achieve the above-mentioned purpose, the present invention provides an anti-corrosion and anti-wear method based on high molecular polymer materials, comprising: receiving an anti-corrosion and anti-wear instruction, and preparing a coating spray based on the anti-corrosion and anti-wear instruction, obtaining an original polymer material group, and setting an original coating thickness, wherein the coating spray comprises: an adhesion coating spray and a resistance coating spray, and the original polymer material is in the form of a rectangular plate; based on the original coating thickness, each original polymer material in the original polymer material group is sprayed with a coating spray to obtain a target polymer material group, wherein the surface of the target polymer material is covered with a coating, and the thickness of the coating is the original coating thickness; the target polymer material group is experimentally grouped to obtain an anti-corrosion material group and an anti-wear material group; the anti-corrosion material group is subjected to corrosion treatment to obtain a material anti-corrosion rate group, wherein the number of material anti-corrosion rates in the material anti-corrosion rate group is the same as the number of anti-corrosion materials; the anti-wear material group is subjected to friction treatment to obtain a material wear rate group, wherein the material wear rate in the material wear rate group is The number of rates is the same as the number of anti-wear materials; based on the material anti-corrosion rate group and the material wear rate group, anti-corrosion and anti-wear analysis is performed to obtain an anti-corrosion and wear factor; the original coating thickness and the anti-corrosion and wear factor are paired to obtain a thickness factor group, and the thickness factor group is added to the pre-constructed original thickness factor group set to obtain a target thickness factor group set; it is determined whether the anti-corrosion and wear factor is greater than a preset standard corrosion factor; if the anti-corrosion and wear factor is not greater than the standard corrosion factor, the original coating thickness is increased according to the target thickness factor group set to obtain a target coating thickness; the original coating thickness and the original thickness factor group set are respectively updated using the target coating thickness and the target thickness factor group set, and the step of spraying each original polymer material in the original polymer material group using a coating spray based on the original coating thickness is returned; if the anti-corrosion and wear factor is greater than the standard corrosion factor, the original coating thickness is recorded as the optimal coating thickness, and the anti-corrosion and anti-wear based on polymer materials is completed based on the optimal coating thickness.

[0006] Optionally, the preparation of the coating spray comprises: obtaining raw materials for preparing the spray, wherein the raw materials for preparing the spray comprise: epoxy resin, deionized water, 3-aminopropyltriethoxysilane, nano-sized titanium dioxide particles, precipitated silica particles, phosphoric acid, silane coupling agent KH-570, methyl methacrylate and glycidyl methacrylate; adding the epoxy resin to deionized water to obtain an original resin mixture, and subjecting the original resin mixture to ultrasonic vibration and constant temperature stirring to obtain a dissolved resin mixture, wherein the ultrasonic vibration and constant temperature stirring are respectively performed by using an ultrasonic oscillator for ultrasonic vibration and using a constant temperature magnetic stirrer for constant temperature stirring; 3-aminopropyltriethoxysilane is added to the dissolved resin mixture to obtain an adhesion coating spray; the phosphoric acid and deionized water are mixed to obtain a base mixture, and nano-scale titanium dioxide particles and precipitated silica particles are added to the base mixture to obtain an original particle mixture, and the original particle mixture is subjected to ultrasonic oscillation treatment to obtain a uniform particle mixture; silane coupling agent KH-570 and methyl methacrylate are dropped into the uniform particle mixture to obtain an original resistance mixture, and the original resistance mixture is stirred at a constant temperature to obtain a uniform resistance mixture; the glycidyl methacrylate is added to the uniform resistance mixture to obtain a resistance coating spray.

[0007] Optionally, the method of spraying each original polymer material in the original polymer material group with the coating spray to obtain the target polymer material group includes: setting the spraying height, the static curing time and the high-temperature curing time, and extracting the original polymer materials in the original polymer material group in sequence; based on the spraying height, using a pre-constructed spraying device to evenly spray the adhesion coating spray on the surface of the original polymer material to obtain a liquid film polymer material, and based on the static curing time, allowing the liquid film polymer material to stand at room temperature to obtain a preliminary cured material; using the resistance coating spray and the preliminary cured material to update the adhesion coating spray and the original polymer material respectively, and returning to the method of evenly spraying the adhesion coating spray on the surface of the original polymer material based on the spraying height using the pre-constructed spraying device The step of: curing the surface of the original polymer material; based on the high-temperature curing time, and using the pre-acquired drying device, the preliminary cured material is subjected to high-temperature curing at a preset curing temperature to obtain a fully cured material; measuring the material coating thickness of the fully cured material, and judging whether the material coating thickness is less than the original coating thickness; if the material coating thickness is less than the original coating thickness, the original polymer material is updated with the fully cured material, and the step of returning to the spraying height-based, pre-constructed spraying device to uniformly spray the adhesion coating spray on the surface of the original polymer material; if the material coating thickness is not less than the original coating thickness, the fully cured material is recorded as the target polymer material, and the target polymer materials are summarized to obtain a target polymer material group.

[0008] Optionally, the corrosion treatment of the anti-corrosion material group to obtain the material corrosion resistance rate group includes: setting the material environmental pH and preparing an environmental salt solution based on the material environmental pH; extracting the anti-corrosion materials in the anti-corrosion material group in turn, and obtaining a control material of the anti-corrosion material, wherein the anti-corrosion material and the control material have the same mass and shape; immersing the anti-corrosion material and the control material in the environmental salt solution respectively to obtain a test anti-corrosion material and a test control material; at each corrosion duration in a preset corrosion duration group, detecting the test corrosion resistance quality and the test control quality of the test anti-corrosion material and the test control material respectively to obtain a test corrosion resistance quality group and a test control quality group; performing material corrosion resistance analysis based on the test corrosion resistance quality group and the test control quality group to obtain a material corrosion resistance rate; summarizing the material corrosion resistance rates to obtain a material corrosion resistance rate group.

[0009] Optionally, the material corrosion resistance analysis is performed according to the test corrosion resistance quality group and the test control quality group to obtain the material corrosion resistance rate, including: extracting the test corrosion resistance quality in the test corrosion resistance quality group in sequence, and identifying the predecessor corrosion resistance quality of the test corrosion resistance quality, wherein the predecessor corrosion resistance quality is the test corrosion resistance quality measured for the last time before the test corrosion resistance quality is measured; identifying the current corrosion time and the predecessor corrosion time of the test corrosion resistance quality and the predecessor corrosion resistance quality respectively, and extracting the current control quality and the predecessor control quality in the test control quality group based on the current corrosion time and the predecessor corrosion time; calculating the unit corrosion resistance rate according to the test corrosion resistance quality, the predecessor corrosion resistance quality, the current corrosion time, the predecessor corrosion time, the current control quality and the predecessor control quality, wherein the unit corrosion resistance rate is expressed as:

[0010] ,in, Represents the unit corrosion resistance rate, Indicates the current control quality, Indicates the quality of the preceding control. Indicates the test anti-corrosion quality, Indicates the anti-corrosion quality of the previous order, Indicates the current corrosion duration. Represents the duration of the preceding corrosion; summarizes the unit corrosion resistance rates to obtain a unit corrosion resistance rate set, calculates the average corrosion resistance rate of the unit corrosion resistance rate set, and records the average corrosion resistance rate as the material corrosion resistance rate.

[0011] Optionally, the friction treatment of the anti-wear material group to obtain the material wear rate group includes: setting friction test parameters of a pre-constructed friction test device, wherein the friction test parameters include: friction time, friction load, friction frequency, friction speed and friction temperature, and the friction test device is a ball-disc friction and wear tester; extracting anti-wear materials from the anti-wear material group in sequence, starting the friction test device based on the friction test parameters, and using the friction test device to rub the anti-wear material to obtain wear material; measuring the wear material volume of the wear material, and obtaining the contact area between the friction test device and the anti-wear material, and calculating the material wear rate according to the wear material volume, the contact area and the preset original material volume, wherein the material wear rate is expressed as:

[0012] ,in, represents the material wear rate, represents the original material volume, represents the volume of wear material, represents the friction load, represents the contact area; and the material wear rates are summarized to obtain a material wear rate group.

[0013] Optionally, the anti-corrosion and anti-wear analysis is performed based on the material anti-corrosion rate group and the material wear rate group to obtain the anti-corrosion and wear factor, including: setting an anti-corrosion weight factor and an anti-wear weight factor; and calculating the anti-corrosion and wear factor according to the anti-corrosion weight factor, the anti-wear weight factor, the material anti-corrosion rate group and the material wear rate group using the following formula:

[0014] , ,in, Represents the anti-corrosion factor, Indicates the number of material corrosion resistance rates in the material corrosion resistance rate group. Indicates the number of material wear rates in the material wear rate group, represents the anti-corrosion weight factor, represents the corrosion rate of the i-th material in the material corrosion rate group, represents the anti-wear weight factor, Represents the jth material wear rate in the material wear rate group.

[0015] Optionally, increasing the original coating thickness according to the target thickness factor set to obtain the target coating thickness includes: obtaining the target group number of the target thickness factor set, and determining whether the target group number is greater than a preset standard group number; if the target group number is not greater than the standard group number, increasing the original coating thickness according to the target group number and the standard group number to obtain the target coating thickness, wherein the target coating thickness is expressed as:

[0016] ,in, represents the target coating thickness, Indicates the number of standard groups, Indicates the number of target groups, Represents the original coating thickness; if the target group number is greater than the standard group number, the original coating thickness is increased based on the target thickness factor set to obtain the target coating thickness.

[0017] Optionally, increasing the original coating thickness based on the target thickness factor set to obtain the target coating thickness includes: extracting a historical coating thickness set and a historical corrosion factor set of the target thickness factor set, and calculating a factor variation coefficient set based on the historical coating thickness set and the historical corrosion factor set, wherein the factor variation coefficient set is expressed as:

[0018] ,in, represents the set of factor variation coefficients, represents the u-th factor change coefficient in the factor change coefficient set, Indicates the first Historical corrosion factor, represents the u-th historical corrosion factor, The first Historical coating thickness, represents the uth historical coating thickness, represents the number of target groups; identifies the effective variation coefficient in the factor variation coefficient set, and calculates the target coating thickness according to the effective variation coefficient, the original coating thickness, the anti-corrosion factor and the standard corrosion factor, wherein the effective variation coefficient and the target coating thickness are respectively expressed as:

[0019] , ,in, represents the effective coefficient of variation, Indicates the concentration of factor variation coefficient The coefficient of variation of the factor, represents the target coating thickness, Represents the standard corrosion factor.

[0020] To achieve the above-mentioned purpose, the present invention also provides an anti-corrosion and anti-wear system based on high molecular polymer materials, including: a coating spray preparation module, which is used to receive anti-corrosion and anti-wear instructions, and prepare coating sprays based on the anti-corrosion and anti-wear instructions, obtain the original polymer material group, and set the original coating thickness, wherein the coating spray includes: an adhesion coating spray and a resistance coating spray, and the original polymer material is in the form of a rectangular plate, based on the original coating thickness, each original polymer material in the original polymer material group is sprayed with a coating spray to obtain a target polymer material group, wherein the surface of the target polymer material is covered with a coating, and the thickness of the coating is the original coating thickness; a corrosion and wear data acquisition module, which is used to test group the target polymer material group to obtain an anti-corrosion material group and an anti-wear material group, perform corrosion treatment on the anti-corrosion material group to obtain a material anti-corrosion rate group, wherein the number of material anti-corrosion rates in the material anti-corrosion rate group is the same as the number of anti-corrosion materials, perform friction treatment on the anti-wear material group to obtain a material wear rate group, wherein, The number of material wear rates in the material wear rate group is the same as the number of wear-resistant materials; a target thickness calculation module is used to perform corrosion and wear analysis based on the material corrosion resistance rate group and the material wear rate group to obtain the corrosion resistance factor, pair the original coating thickness and the corrosion resistance factor to obtain the thickness factor group, and add the thickness factor group to the pre-constructed original thickness factor group set to obtain the target thickness factor group set, and judge whether the corrosion resistance factor is greater than the preset standard corrosion factor. If the corrosion resistance factor is not greater than the standard corrosion factor, the original coating thickness is increased according to the target thickness factor group set to obtain the target coating thickness; an optimal thickness confirmation module is used to update the original coating thickness and the original thickness factor group set respectively using the target coating thickness and the target thickness factor group set, and return the step of spraying each original polymer material in the original polymer material group with a coating spray based on the original coating thickness. If the corrosion resistance factor is greater than the standard corrosion factor, the original coating thickness is recorded as the optimal coating thickness.

[0021] In order to solve the above problems, the present invention also provides an electronic device, which includes: a memory storing at least one instruction; and a processor executing the instructions stored in the memory to implement the above-mentioned anti-corrosion and anti-wear method based on polymer materials.

[0022] In order to solve the above problems, the present invention also provides a computer-readable storage medium, in which at least one instruction is stored. The at least one instruction is executed by a processor in an electronic device to implement the above-mentioned anti-corrosion and anti-wear method based on polymer materials.

[0023] In order to solve the problems described in the background technology, the present invention firstly sprays the original polymer material based on the original coating thickness and uses a coating spray to obtain a target polymer material. The surface of the target polymer material will be covered with a coating with a thickness equal to the original coating thickness. The coating can effectively improve the corrosion resistance and wear resistance of the original polymer material. Then, the target polymer material is grouped to obtain an anti-corrosion material group and an anti-wear material group. Corrosion tests and friction tests are performed on the anti-corrosion material group and the anti-wear material group respectively to obtain a material anti-corrosion rate group and a material wear rate group. In this step, the degree of improvement of the corrosion resistance and wear resistance of the original polymer material by the coating with a thickness equal to the original coating thickness is quantified, and through the tests of multiple anti-corrosion materials and anti-wear materials, the accuracy of subsequent anti-corrosion and wear resistance analysis is improved. Through the material anti-corrosion rate group and material wear rate The anti-corrosion and wear resistance factor is calculated. This step integrates the anti-corrosion and wear resistance of the target polymer material and provides a comprehensive evaluation index for the material performance. When calculating the anti-corrosion and wear resistance factor, a weight factor is introduced to reflect the different requirements for anti-corrosion and wear resistance in different application scenarios. This makes the anti-corrosion and wear resistance factor more in line with the actual application needs and enhances the anti-corrosion and wear resistance of the polymer material in a specific environment. Finally, by comparing the anti-corrosion and wear resistance factor with the standard corrosion and wear resistance factor, the optimal coating thickness of the polymer material is accurately determined. The determination of the optimal coating thickness ensures that the anti-corrosion and wear resistance of the material matches the predetermined standard anti-corrosion and wear resistance factor, thereby controlling the cost of anti-corrosion and wear resistance while meeting the performance requirements, that is, the determination of the optimal coating thickness avoids unnecessary material consumption and cost increase caused by excessively thick coatings. Therefore, the present invention can improve the anti-corrosion and wear resistance of polymer materials and reduce the cost of anti-corrosion and wear resistance of polymer materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 A schematic flow chart of an anti-corrosion and anti-wear method based on a polymer material provided in one embodiment of the present invention; Figure 2 A functional module diagram of an anti-corrosion and anti-wear system based on a polymer material provided by an embodiment of the present invention; Figure 3 A schematic structural diagram of an electronic device for implementing the anti-corrosion and anti-wear method based on high molecular polymer materials provided in one embodiment of the present invention.

[0025] Explanation of the reference numerals: 1. electronic device; 10. processor; 11. memory; 12. bus.

[0026] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0027] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.

[0028] The embodiment of the present application provides an anti-corrosion and anti-wear method based on polymer materials. The execution subject of the anti-corrosion and anti-wear method based on polymer materials includes but is not limited to at least one of the electronic devices such as a server and a terminal that can be configured to execute the method provided in the embodiment of the present application. In other words, the anti-corrosion and anti-wear method based on polymer materials can be executed by software or hardware installed on a terminal device or a server device, and the software can be a blockchain platform. The server includes but is not limited to: a single server, a server cluster, a cloud server or a cloud server cluster, etc.

[0029] Reference Figure 1 , which is a flow chart of an anti-corrosion and anti-wear method based on a polymer material according to an embodiment of the present invention. In this embodiment, the anti-corrosion and anti-wear method based on a polymer material comprises: S1, receiving an anti-corrosion and anti-wear instruction, preparing a coating spray based on the anti-corrosion and anti-wear instruction, obtaining an original polymer material group, and setting an original coating thickness, wherein the coating spray comprises: an adhesion coating spray and a resistance coating spray, and the original polymer material is in the form of a rectangular plate.

[0030] It can be understood that the anti-corrosion and anti-wear instructions refer to human-initiated instructions aimed at performing anti-corrosion and anti-wear treatments on polymer materials, wherein the anti-corrosion and anti-wear treatments are achieved by spraying the surface of the polymer with a coating spray, wherein the coating spray refers to a liquid material that can be evenly applied to the surface of the polymer material by spraying, and the coating spray contains chemical substances that can resist corrosion and wear, so it can effectively reduce the impact of environmental factors such as humidity, temperature, chemical substances, etc., as well as physical wear on the surface of the material.

[0031] It can be understood that the original polymer material group refers to a plurality of high molecular polymer materials that need to be treated with corrosion and wear protection. Since it is necessary to test the corrosion and wear resistance of a plurality of different original polymer materials, and in order to ensure the accuracy and reliability of the test data and eliminate accidental factors, it is necessary to collect a plurality of original polymer material samples. The original polymer material refers to unprocessed or preliminarily processed high molecular polymers, which are the basic materials for manufacturing various plastics, rubbers, fibers and other products, such as polyethylene (PE) and polypropylene (PP). They can be synthesized through experiments or purchased from relevant suppliers.

[0032] It should be explained that the original coating thickness refers to an artificially set thickness constant, which indicates the thickness of the coating on the surface of the original polymer material when the original polymer material is sprayed. Materials with thinner coating thickness have relatively poor corrosion and wear resistance, while materials with thicker coating thickness have better protective effects. However, excessive coating thickness will not only increase costs, but may also lead to reduced production efficiency. Therefore, it is necessary to find a balance point that can ensure the protective performance of the coating while controlling costs and improving production efficiency.

[0033] Furthermore, the adhesion coating spray refers to a spray that can be tightly bonded to the original polymer material and can also provide corrosion resistance to the original polymer material. The resistance coating spray refers to a spray sprayed on the adhesion coating spray, which can provide the original polymer material with stronger corrosion resistance and wear resistance.

[0034] For example, Xiao Zhang is a research and development staff of a materials company. One day, Xiao Zhang received an anti-corrosion and anti-wear instruction, which required anti-corrosion and anti-wear operations on a polymer material. So Xiao Zhang prepared a coating spray and obtained multiple polymer materials of this model, setting the original coating thickness to 50 μm.

[0035] In detail, the preparation of the coating spray comprises: obtaining raw materials for preparing the spray, wherein the raw materials for preparing the spray comprise: epoxy resin, deionized water, 3-aminopropyltriethoxysilane, nano-sized titanium dioxide particles, precipitated silica particles, phosphoric acid, silane coupling agent KH-570, methyl methacrylate and glycidyl methacrylate; adding the epoxy resin to deionized water to obtain an original resin mixture, and subjecting the original resin mixture to ultrasonic vibration and constant temperature stirring to obtain a dissolved resin mixture, wherein the ultrasonic vibration and constant temperature stirring are respectively: ultrasonic vibration using an ultrasonic oscillator and constant temperature stirring using a constant temperature magnetic stirrer; 3-aminopropyltriethoxysilane is added to the dissolved resin mixture to obtain an adhesion coating spray; the phosphoric acid and deionized water are mixed to obtain a base mixture, and nano-scale titanium dioxide particles and precipitated silica particles are added to the base mixture to obtain an original particle mixture, and the original particle mixture is subjected to ultrasonic oscillation treatment to obtain a uniform particle mixture; silane coupling agent KH-570 and methyl methacrylate are dropped into the uniform particle mixture to obtain an original resistance mixture, and the original resistance mixture is stirred at a constant temperature to obtain a uniform resistance mixture; the glycidyl methacrylate is added to the uniform resistance mixture to obtain a resistance coating spray.

[0036] It can be understood that the epoxy resin has good chemical resistance and aging resistance, the deionized water helps to improve the adhesion and uniformity of the coating, and the deionized water and epoxy resin are mixed to obtain a dissolved resin mixture with high adhesion and corrosion resistance. The 3-aminopropyltriethoxysilane can further improve the material surface adhesion ability of the dissolved resin mixture. The nano-scale titanium dioxide particles have excellent ultraviolet shielding properties and can improve the aging resistance of the coating. The precipitated silica particles have high hardness and can significantly improve the wear resistance of the coating. The phosphoric acid can be used as a corrosion inhibitor to improve the corrosion resistance of the coating. The silane coupling agent KH-570 is a multifunctional silane coupling agent that can improve the water resistance and adhesion of the coating. The methyl methacrylate can provide strong corrosion resistance for the coating. The glycidyl methacrylate can increase the cross-linking density of the coating, thereby enhancing the mechanical strength and wear resistance of the original polymer material.

[0037] Exemplarily, Xiao Zhang obtains the raw materials for preparing the spray. First, Xiao Zhang prepares the adhesion coating spray: 0.3 g of epoxy resin is added to 10 ml of deionized water to obtain an original resin mixture, and the original resin mixture is treated with an ultrasonic oscillator for 30 minutes to ensure that the epoxy resin is completely dispersed, and the original resin mixture is heated at 70 The mixture was stirred for 30 minutes using a constant temperature magnetic stirrer to obtain a dissolved resin mixture, and then 0.2 ml of 3-aminopropyltriethoxysilane was added to the dissolved resin mixture to obtain an adhesion coating spray. Xiao Zhang then prepared a resistance coating spray: 15 ml of phosphoric acid and 45 ml of deionized water were mixed to obtain a base mixture, and 0.4 g of nano-sized titanium dioxide particles and 0.6 g of precipitated silica particles were added to the base mixture to obtain a primary particle mixture, and the primary particle mixture was ultrasonically oscillated using an ultrasonic oscillator for 45 minutes to obtain a uniform particle mixture, and 3 ml of silane coupling agent KH-570 and 1 ml of methyl methacrylate were added dropwise to the uniform particle mixture using a rubber-tipped dropper, and a constant temperature magnetic stirrer was used at 70 °C to stir the mixture. The mixture was stirred for 6 hours to obtain a uniform resistant mixture, and finally 0.3 ml of glycidyl methacrylate was added to the uniform resistant mixture and stirred for 3 hours to obtain a resistant coating spray.

[0038] S2. Based on the original coating thickness, each original polymer material in the original polymer material group is sprayed with a coating spray to obtain a target polymer material group, wherein the surface of the target polymer material is covered with a coating, and the thickness of the coating is the original coating thickness.

[0039] It can be understood that the target polymer material refers to the original polymer material after being sprayed with the coating spray.

[0040] In detail, the method of using a coating spray to spray each original polymer material in the original polymer material group to obtain a target polymer material group includes: setting a spraying height, a static curing time, and a high-temperature curing time, and extracting original polymer materials in the original polymer material group in sequence; based on the spraying height, using a pre-constructed spraying device to evenly spray the adhesion coating spray on the surface of the original polymer material to obtain a liquid film polymer material, and based on the static curing time, allowing the liquid film polymer material to stand at room temperature to obtain a preliminary cured material; using a resistant coating spray and a preliminary cured material to update the adhesion coating spray and the original polymer material respectively, and returning to the method of evenly spraying the adhesion coating spray on the surface of the original polymer material based on the spraying height using a pre-constructed spraying device The step of: curing the surface of the original polymer material; based on the high-temperature curing time, and using the pre-acquired drying device, the preliminary cured material is subjected to high-temperature curing at a preset curing temperature to obtain a fully cured material; measuring the material coating thickness of the fully cured material, and judging whether the material coating thickness is less than the original coating thickness; if the material coating thickness is less than the original coating thickness, the original polymer material is updated with the fully cured material, and the step of returning to the spraying height-based, pre-constructed spraying device to uniformly spray the adhesion coating spray on the surface of the original polymer material; if the material coating thickness is not less than the original coating thickness, the fully cured material is recorded as the target polymer material, and the target polymer materials are summarized to obtain a target polymer material group.

[0041] It can be understood that the spraying height refers to the distance between the surface of the original polymer material and the spraying device, wherein the spraying device refers to a tool for spraying the coating spray onto the surface of the original polymer material, such as a spray gun, and the static curing time refers to the time for standing the liquid film polymer material at room temperature, such as 20 minutes, and the high-temperature curing time refers to the time for high-temperature curing of the preliminary cured material, such as 40 minutes, wherein the tool for high-temperature curing is a drying device, which can be an electric constant temperature blower dryer, and the material coating thickness refers to the coating thickness on the surface of the completely cured material.

[0042] For example, the spraying height, static curing time and high temperature curing time of a material factory are set to 20 cm, 20 min and 40 min respectively. The operator Xiao Wang of the factory places the original polymer material horizontally and places the spray gun vertically 20 cm above the original polymer material. Then, the spray gun is started to spray the adhesion coating spray evenly on the surface of the original polymer material to obtain a liquid film polymer material. The liquid film polymer material is placed at room temperature and left to stand for 20 min to obtain a preliminary cured material. Then, the above steps are repeated to spray the resistance coating spray on the surface of the preliminary cured material. Then, the electric constant temperature blower dryer is used to dry the material at 100 °C. The preliminary cured material is subjected to high temperature curing for 40 minutes to obtain a fully cured material, and the above steps are repeated until the surface thickness of the fully cured material is not less than the original coating thickness.

[0043] S3. Experimentally grouping the target polymer material group to obtain an anti-corrosion material group and an anti-wear material group.

[0044] It should be explained that the anti-corrosion material refers to the target polymer material that needs to undergo an anti-corrosion test, and the anti-wear material refers to the target polymer material that needs to undergo an anti-wear test. The step of grouping the tests is: dividing the target polymer material group equally to obtain an anti-corrosion material group and an anti-wear material group, wherein the sum of the number of anti-corrosion materials and anti-wear materials is the number of target polymer materials.

[0045] S4. Perform corrosion treatment on the anti-corrosion material group to obtain a material anti-corrosion rate group, wherein the number of material anti-corrosion rates in the material anti-corrosion rate group is the same as the number of anti-corrosion materials.

[0046] It should be explained that the material corrosion resistance rate refers to a value used to indicate that the coating can reduce the degree of corrosion of the original polymer material.

[0047] In detail, the corrosion treatment of the anti-corrosion material group to obtain the material corrosion resistance rate group includes: setting the material environmental pH and preparing an environmental salt solution based on the material environmental pH; extracting the anti-corrosion materials in the anti-corrosion material group in turn, and obtaining the control material of the anti-corrosion material, wherein the anti-corrosion material and the control material have the same mass and shape; immersing the anti-corrosion material and the control material in the environmental salt solution respectively to obtain the test anti-corrosion material and the test control material; at each corrosion time in the preset corrosion time group, detecting the test corrosion resistance quality and the test control quality of the test anti-corrosion material and the test control material respectively to obtain the test corrosion resistance quality group and the test control quality group; performing material corrosion resistance analysis based on the test corrosion resistance quality group and the test control quality group to obtain the material corrosion resistance rate; summarizing the material corrosion resistance rates to obtain the material corrosion resistance rate group.

[0048] It can be understood that the environmental pH refers to the artificially set pH, which is determined according to the use environment of the target polymer material finally obtained. The environmental salt solution refers to a salt solution with a pH of the environmental pH, for example: sodium chloride solution, which can be made to have a pH of the environmental pH by adding an acid solution or an alkaline solution to the sodium chloride solution. The control material refers to a high molecular polymer material with the same composition, size, mass and shape as the anti-corrosion material, which is intended to provide a control group for the anti-corrosion material. The corrosion time group refers to a combination of multiple artificially set corrosion times, wherein the corrosion time refers to the total time that the current anti-corrosion material has been immersed in the environmental salt solution. The test anti-corrosion quality refers to the quality of the test anti-corrosion material during the corrosion time, and the test control quality refers to the quality of the test control material during the corrosion time.

[0049] In detail, the material corrosion resistance analysis is performed according to the test corrosion resistance quality group and the test control quality group to obtain the material corrosion resistance rate, including: extracting the test corrosion resistance quality in the test corrosion resistance quality group in turn, and identifying the predecessor corrosion resistance quality of the test corrosion resistance quality, wherein the predecessor corrosion resistance quality is the test corrosion resistance quality measured for the last time before the test corrosion resistance quality is measured; identifying the current corrosion time and the predecessor corrosion time of the test corrosion resistance quality and the predecessor corrosion resistance quality respectively, and extracting the current control quality and the predecessor control quality in the test control quality group based on the current corrosion time and the predecessor corrosion time; calculating the unit corrosion resistance rate according to the test corrosion resistance quality, the predecessor corrosion resistance quality, the current corrosion time, the predecessor corrosion time, the current control quality and the predecessor control quality, wherein the unit corrosion resistance rate is expressed as:

[0050] ,in, Represents the unit corrosion resistance rate, Indicates the current control quality, Indicates the quality of the preceding control. Indicates the test anti-corrosion quality, Indicates the anti-corrosion quality of the previous order, Indicates the current corrosion duration. Indicates the duration of the preceding corrosion;

[0051] The unit anti-corrosion rates are summarized to obtain a unit anti-corrosion rate set, the average anti-corrosion rate of the unit anti-corrosion rate set is calculated, and the average anti-corrosion rate is recorded as the material anti-corrosion rate.

[0052] It can be understood that the previous anti-corrosion quality refers to the test anti-corrosion quality measured last time before the test anti-corrosion quality is measured, the current corrosion time refers to the corrosion time when the test anti-corrosion quality is measured in the corrosion time group, and the previous corrosion time refers to the corrosion time when the test control quality is measured in the corrosion time group.

[0053] S5. Performing friction treatment on the anti-wear material group to obtain a material wear rate group, wherein the number of material wear rates in the material wear rate group is the same as the number of anti-wear materials.

[0054] It should be explained that the material wear rate refers to a numerical value used to indicate the degree of wear of the anti-wear material under specific conditions, wherein the specific conditions refer to relevant parameters artificially set during the friction treatment process.

[0055] In detail, the friction treatment of the anti-wear material group to obtain the material wear rate group includes: setting the friction test parameters of the pre-constructed friction test device, wherein the friction test parameters include: friction time, friction load, friction frequency, friction speed and friction temperature, and the friction test device is a ball-disc friction and wear tester; extracting anti-wear materials from the anti-wear material group in sequence, starting the friction test device based on the friction test parameters, and using the friction test device to rub the anti-wear material to obtain the wear material; measuring the wear material volume of the wear material, and obtaining the contact area between the friction test device and the anti-wear material, and calculating the material wear rate according to the wear material volume, the contact area and the preset original material volume, wherein the material wear rate is expressed as:

[0056] ,in, represents the material wear rate, represents the original material volume, represents the volume of wear material, represents the friction load, represents the contact area; and the material wear rates are summarized to obtain a material wear rate group.

[0057] It can be understood that the friction testing device refers to a device for performing wear tests on anti-wear materials, and a ball-disc friction and wear testing machine can be selected as the friction testing device, wherein the friction duration refers to the duration of the friction test, the friction load refers to the force applied to the anti-wear material in the friction test, the friction frequency refers to the number of times the friction contact point contacts the anti-wear material per unit time, the friction speed refers to the rotation speed of the friction ball in the ball-disc friction and wear testing machine, the friction temperature refers to the temperature of the contact area between the friction testing device and the anti-wear material during the friction process, the wear material volume refers to the volume of the wear material, and the original material volume refers to the volume of the anti-wear material.

[0058] S6. Based on the material corrosion rate group and the material wear rate group, anti-corrosion and anti-wear analysis is performed to obtain the anti-corrosion and wear factor.

[0059] It should be explained that the anti-corrosion factor refers to a value used to indicate the anti-corrosion and anti-wear capabilities of the target polymer material.

[0060] In detail, the anti-corrosion and anti-wear analysis is performed based on the material anti-corrosion rate group and the material wear rate group to obtain the anti-corrosion and wear factor, including: setting the anti-corrosion weight factor and the anti-wear weight factor; according to the anti-corrosion weight factor, the anti-wear weight factor, the material anti-corrosion rate group and the material wear rate group, the anti-corrosion and wear factor is calculated using the following formula:

[0061] , ,in, Represents the anti-corrosion factor, Indicates the number of material corrosion resistance rates in the material corrosion resistance rate group. Indicates the number of material wear rates in the material wear rate group, represents the anti-corrosion weight factor, represents the corrosion rate of the i-th material in the material corrosion rate group, represents the anti-wear weight factor, Represents the jth material wear rate in the material wear rate group.

[0062] Furthermore, the anti-corrosion weight factor and anti-wear weight factor refer to artificially set numerical values ​​used to indicate the importance of anti-corrosion ability and anti-wear ability in practical applications. They are indicators that quantify the relative importance of corrosion resistance and wear resistance in specific applications. Since different usage environments have different requirements for the corrosion and wear resistance of the target polymer material, the anti-corrosion weight factor and anti-wear weight factor can be artificially set according to actual conditions.

[0063] For example, for polymer materials used in offshore platforms, since the polymer materials need to be exposed to a high-salt, high-humidity marine environment for a long time and are susceptible to corrosion, the anti-corrosion weight factor of the polymer material needs to be set higher, such as the anti-corrosion weight factor is 0.7, and the anti-wear weight factor is set to 0.3. For polymer materials in automobile braking systems, since the automobile braking system will experience high-intensity friction and wear during operation, the anti-wear weight factor of the polymer material can be set higher, such as the anti-corrosion weight factor is 0.3, and the anti-wear weight factor is 0.7.

[0064] S7. Pair the original coating thickness and the anti-corrosion factor to obtain a thickness factor group, and add the thickness factor group to the pre-constructed original thickness factor group set to obtain a target thickness factor group set.

[0065] It should be explained that the original thickness factor set refers to the combination of the original coating thickness and the anti-corrosion factor obtained before the thickness factor group is obtained. The original thickness factor set is an empty set when the original coating thickness and the anti-corrosion factor are not obtained. The target thickness factor set refers to the original thickness factor set after supplementation.

[0066] S8. Determine whether the anti-corrosion factor is greater than a preset standard corrosion factor.

[0067] It can be understood that the standard corrosion factor refers to an artificially set corrosion factor constant. When the anti-corrosion factor is not greater than the standard corrosion factor, it means that the current coating thickness cannot meet the needs of actual application and the coating thickness needs to be increased. When the anti-corrosion factor is greater than the standard corrosion factor, it means that the current coating thickness can already meet the needs of actual application. In order to ensure that the cost of corrosion and wear prevention is low, the current coating thickness can be used as the final optimal coating thickness.

[0068] If the anti-corrosion factor is not greater than the standard corrosion factor, S9 is executed to increase the original coating thickness according to the target thickness factor set to obtain the target coating thickness.

[0069] It is understood that the target coating thickness refers to the increased original coating thickness.

[0070] In detail, the method of increasing the original coating thickness according to the target thickness factor set to obtain the target coating thickness includes: obtaining the target group number of the target thickness factor set, and judging whether the target group number is greater than the preset standard group number; if the target group number is not greater than the standard group number, increasing the original coating thickness according to the target group number and the standard group number to obtain the target coating thickness, wherein the target coating thickness is expressed as:

[0071] ,in, represents the target coating thickness, Indicates the number of standard groups, Indicates the number of target groups, Represents the original coating thickness; if the target group number is greater than the standard group number, the original coating thickness is increased based on the target thickness factor set to obtain the target coating thickness.

[0072] It should be explained that the target group number refers to the number of target thickness factor groups in the target thickness factor group set, and the standard group number refers to an artificially set group number constant.

[0073] It should be explained that when the number of target groups is small, there is a lack of sufficient data to determine the exact relationship between coating thickness and anti-corrosion factor. Therefore, the coating thickness can be gradually increased through artificially set steps to generate more thickness factor groups, thereby expanding the target thickness factor group set. As the number of target groups increases and approaches the number of standard groups, the increase in coating thickness needs to be adjusted more carefully. At this time, the increase in target coating thickness will become less and less. As time goes by, after accumulating more target thickness factor groups, these target thickness factor groups need to be used to guide subsequent coating thickness adjustments, which can ensure that the thickness increase is more precise.

[0074] In detail, the method of increasing the original coating thickness based on the target thickness factor set to obtain the target coating thickness includes: extracting the historical coating thickness set and the historical corrosion factor set of the target thickness factor set, and calculating the factor variation coefficient set based on the historical coating thickness set and the historical corrosion factor set, wherein the factor variation coefficient set is expressed as:

[0075] ,in, represents the set of factor variation coefficients, represents the u-th factor change coefficient in the factor change coefficient set, Indicates the first Historical corrosion factor, represents the u-th historical corrosion factor, The first Historical coating thickness, represents the uth historical coating thickness, represents the number of target groups; identifies the effective variation coefficient in the factor variation coefficient set, and calculates the target coating thickness according to the effective variation coefficient, the original coating thickness, the anti-corrosion factor and the standard corrosion factor, wherein the effective variation coefficient and the target coating thickness are respectively expressed as:

[0076] , ,in, represents the effective coefficient of variation, Indicates the concentration of factor variation coefficient The coefficient of variation of the factor, represents the target coating thickness, Represents the standard corrosion factor.

[0077] It should be explained that the historical coating thickness set refers to the set of all coating thicknesses appearing in the target thickness factor group set, the historical corrosion factor set refers to the set of all anti-corrosion factors appearing in the target thickness factor group set, the factor variation coefficient refers to a numerical value used to represent the variation relationship between two connected coating thicknesses and two anti-corrosion factors, and the effective variation coefficient refers to a numerical value that is less than the average variation coefficient in the factor variation coefficient set, which is used to ensure that the anti-corrosion factor corresponding to the target coating thickness calculated subsequently will not deviate too much from the standard anti-corrosion factor.

[0078] S10, respectively updating the original coating thickness and the original thickness factor set using the target coating thickness and the target thickness factor set, and returning to the step of spraying each original polymer material in the original polymer material group using a coating spray based on the original coating thickness.

[0079] It is understandable that after obtaining the target coating thickness when the anti-corrosion factor is not greater than the standard corrosion factor, it is necessary to re-perform corrosion treatment and friction treatment according to the target coating thickness.

[0080] If the anti-corrosion factor is greater than the standard corrosion factor, S11 is executed to record the original coating thickness as the optimal coating thickness, and the anti-corrosion and anti-wear based on the polymer material is completed based on the optimal coating thickness.

[0081] It should be explained that when the anti-corrosion factor is greater than the standard corrosion factor, it means that the optimal coating thickness at this time can meet the actual application requirements. The original polymer material can be sprayed according to the optimal coating thickness to achieve anti-corrosion and anti-wear of the polymer material.

[0082] In order to solve the problems described in the background technology, the present invention firstly sprays the original polymer material based on the original coating thickness and uses a coating spray to obtain a target polymer material. The surface of the target polymer material will be covered with a coating with a thickness equal to the original coating thickness. The coating can effectively improve the corrosion resistance and wear resistance of the original polymer material. Then, the target polymer material is grouped to obtain an anti-corrosion material group and an anti-wear material group. Corrosion tests and friction tests are performed on the anti-corrosion material group and the anti-wear material group respectively to obtain a material anti-corrosion rate group and a material wear rate group. In this step, the degree of improvement of the corrosion resistance and wear resistance of the original polymer material by the coating with a thickness equal to the original coating thickness is quantified, and through the tests of multiple anti-corrosion materials and anti-wear materials, the accuracy of subsequent anti-corrosion and wear resistance analysis is improved. Through the material anti-corrosion rate group and material wear rate The anti-corrosion and wear resistance factor is calculated. This step integrates the anti-corrosion and wear resistance of the target polymer material and provides a comprehensive evaluation index for the material performance. When calculating the anti-corrosion and wear resistance factor, a weight factor is introduced to reflect the different requirements for anti-corrosion and wear resistance in different application scenarios. This makes the anti-corrosion and wear resistance factor more in line with the actual application needs and enhances the anti-corrosion and wear resistance of the polymer material in a specific environment. Finally, by comparing the anti-corrosion and wear resistance factor with the standard corrosion and wear resistance factor, the optimal coating thickness of the polymer material is accurately determined. The determination of the optimal coating thickness ensures that the anti-corrosion and wear resistance of the material matches the predetermined standard anti-corrosion and wear resistance factor, thereby controlling the cost of anti-corrosion and wear resistance while meeting the performance requirements, that is, the determination of the optimal coating thickness avoids unnecessary material consumption and cost increase caused by excessively thick coatings. Therefore, the present invention can improve the anti-corrosion and wear resistance of polymer materials and reduce the cost of anti-corrosion and wear resistance of polymer materials.

[0083] like Figure 2 , which is a functional module diagram of an anti-corrosion and anti-wear system based on polymer materials provided in one embodiment of the present invention.

[0084] The anti-corrosion and anti-wear system 100 based on polymer materials of the present invention can be installed in an electronic device. According to the functions to be implemented, the anti-corrosion and anti-wear system 100 based on polymer materials can include a coating spray preparation module 101, a corrosion and wear data acquisition module 102, a target thickness calculation module 103 and an optimal thickness confirmation module 104. The module of the present invention can also be called a unit, which refers to a series of computer program segments that can be executed by an electronic device processor and can complete fixed functions, which are stored in the memory of the electronic device.

[0085] The coating spray preparation module 101 is used to receive anti-corrosion and anti-wear instructions, and prepare coating sprays based on the anti-corrosion and anti-wear instructions, obtain the original polymer material group, and set the original coating thickness, wherein the coating spray includes: an adhesion coating spray and a resistance coating spray, and the original polymer material is in the form of a rectangular plate, and based on the original coating thickness, each original polymer material in the original polymer material group is sprayed with a coating spray to obtain a target polymer material group, wherein the surface of the target polymer material is covered with a coating, and the thickness of the coating is the original coating thickness; the corrosion and wear data acquisition module 102 is used to test group the target polymer material group to obtain an anti-corrosion material group and an anti-wear material group, perform corrosion treatment on the anti-corrosion material group to obtain a material anti-corrosion rate group, wherein the number of material anti-corrosion rates in the material anti-corrosion rate group is the same as the number of anti-corrosion materials, perform friction treatment on the anti-wear material group to obtain a material wear rate group, wherein the number of material wear rates in the material wear rate group is the same as the number of The number of anti-wear materials is the same; the target thickness calculation module 103 is used to perform anti-corrosion and anti-wear analysis based on the material anti-corrosion rate group and the material wear rate group to obtain the anti-corrosion factor, pair the original coating thickness and the anti-corrosion factor to obtain the thickness factor group, and add the thickness factor group to the pre-constructed original thickness factor group set to obtain the target thickness factor group set, and judge whether the anti-corrosion factor is greater than the preset standard corrosion factor. If the anti-corrosion factor is not greater than the standard corrosion factor, the original coating thickness is increased according to the target thickness factor group set to obtain the target coating thickness; the optimal thickness confirmation module 104 is used to update the original coating thickness and the original thickness factor group set respectively using the target coating thickness and the target thickness factor group set, and return to the step of spraying each original polymer material in the original polymer material group with a coating spray based on the original coating thickness. If the anti-corrosion factor is greater than the standard corrosion factor, the original coating thickness is recorded as the optimal coating thickness.

[0086] In detail, each module in the anti-corrosion and anti-wear system 100 based on polymer materials in the embodiment of the present invention is used in the same manner as described above. Figure 1 The same technical means as the anti-corrosion and anti-wear method based on polymer materials described in the text and can produce the same technical effects will not be repeated here.

[0087] like Figure 3 , which is a schematic diagram of the structure of an electronic device for implementing an anti-corrosion and anti-wear method based on high molecular polymer materials provided by an embodiment of the present invention.

[0088] The electronic device 1 may include a processor 10, a memory 11 and a bus 12, and may also include a computer program stored in the memory 11 and executable on the processor 10, such as a program for an anti-corrosion and anti-wear method based on high molecular polymer materials.

[0089] The memory 11 includes at least one type of readable storage medium, and the readable storage medium includes a flash memory, a mobile hard disk, a multimedia card, a card-type memory (e.g., SD or DX memory, etc.), a magnetic memory, a disk, an optical disk, etc. In some embodiments, the memory 11 may be an internal storage unit of the electronic device 1, such as a mobile hard disk of the electronic device 1. In other embodiments, the memory 11 may also be an external storage device of the electronic device 1, such as a plug-in mobile hard disk, a smart memory card (Smart Media Card, SMC), a secure digital (SecureDigital, SD) card, a flash card (Flash Card), etc. equipped on the electronic device 1. Further, the memory 11 also includes an internal storage unit of the electronic device 1 and an external storage device. The memory 11 can not only be used to store application software and various types of data installed in the electronic device 1, such as the code of the anti-corrosion and anti-wear method program based on polymer materials, but also can be used to temporarily store data that has been output or is to be output.

[0090] The processor 10 may be composed of an integrated circuit in some embodiments, for example, a single packaged integrated circuit, or a plurality of packaged integrated circuits with the same or different functions, including one or more central processing units (CPUs), microprocessors, digital processing chips, graphics processors, and combinations of various control chips, etc. The processor 10 is the control core (Control Unit) of the electronic device, and uses various interfaces and lines to connect various components of the entire electronic device, and executes or executes programs or modules (such as anti-corrosion and anti-wear method programs based on polymer materials, etc.) stored in the memory 11, and calls data stored in the memory 11 to execute various functions of the electronic device 1 and process data.

[0091] The bus 12 may be a peripheral component interconnect (PCI) bus or an extended industry standard architecture (EISA) bus, etc. The bus 12 may be divided into an address bus, a data bus, a control bus, etc. The bus 12 is configured to realize connection and communication between the memory 11 and at least one processor 10, etc.

[0092] Figure 3 Only an electronic device with components is shown, and those skilled in the art will understand that Figure 3 The structure shown does not constitute a limitation on the electronic device 1, and may include fewer or more components than shown in the figure, or combine certain components, or arrange the components differently.

[0093] For example, although not shown, the electronic device 1 may also include a power source (such as a battery) for supplying power to various components. Preferably, the power source may be logically connected to the at least one processor 10 through a power management system, so that the power management system can realize functions such as charging management, discharging management, and power consumption management. The power source may also include any components such as one or more DC or AC power sources, recharging systems, power failure detection circuits, power converters or inverters, and power status indicators. The electronic device 1 may also include a variety of sensors, Bluetooth modules, Wi-Fi modules, etc., which will not be repeated here.

[0094] Furthermore, the electronic device 1 may also include a network interface. Optionally, the network interface may include a wired interface and / or a wireless interface (such as a WI-FI interface, a Bluetooth interface, etc.), which is generally used to establish a communication connection between the electronic device 1 and other electronic devices.

[0095] Optionally, the electronic device 1 may further include a user interface, which may be a display, an input unit (such as a keyboard), or a standard wired interface or a wireless interface. Optionally, in some embodiments, the display may be an LED display, a liquid crystal display, a touch-sensitive liquid crystal display, and an OLED (Organic Light-Emitting Diode) touch device. The display may also be appropriately referred to as a display screen or a display unit, which is used to display information processed in the electronic device 1 and to display a visual user interface.

[0096] The anti-corrosion and anti-wear method program based on high molecular polymer materials stored in the memory 11 in the electronic device 1 is a combination of multiple instructions. When running in the processor 10, it can achieve: receiving anti-corrosion and anti-wear instructions, and preparing a coating spray based on the anti-corrosion and anti-wear instructions, obtaining an original polymer material group, and setting an original coating thickness, wherein the coating spray includes: an adhesion coating spray and a resistance coating spray, and the original polymer material is in the form of a rectangular plate; based on the original coating thickness, each original polymer material in the original polymer material group is sprayed with a coating spray to obtain a target polymer material group, wherein the surface of the target polymer material is covered with a coating, and the thickness of the coating is the original coating thickness; the target polymer material group is experimentally grouped to obtain an anti-corrosion material group and an anti-wear material group; the anti-corrosion material group is subjected to corrosion treatment to obtain a material anti-corrosion rate group, wherein the number of material anti-corrosion rates in the material anti-corrosion rate group is the same as the number of anti-corrosion materials; the anti-wear material group is subjected to friction treatment to obtain a material wear rate group, wherein , the number of material wear rates in the material wear rate group is the same as the number of anti-wear materials; based on the material anti-corrosion rate group and the material wear rate group, anti-corrosion and anti-wear analysis is performed to obtain an anti-corrosion and wear factor; the original coating thickness and the anti-corrosion and wear factor are paired to obtain a thickness factor group, and the thickness factor group is added to the pre-constructed original thickness factor group set to obtain a target thickness factor group set; it is determined whether the anti-corrosion and wear factor is greater than a preset standard corrosion factor; if the anti-corrosion and wear factor is not greater than the standard corrosion factor, the original coating thickness is increased according to the target thickness factor group set to obtain a target coating thickness; the original coating thickness and the original thickness factor group set are respectively updated using the target coating thickness and the target thickness factor group set, and the step of spraying each original polymer material in the original polymer material group with a coating spray based on the original coating thickness is returned; if the anti-corrosion and wear factor is greater than the standard corrosion factor, the original coating thickness is recorded as the optimal coating thickness, and the anti-corrosion and anti-wear based on polymer materials is completed based on the optimal coating thickness.

[0097] Specifically, the specific implementation method of the processor 10 for the above instructions can refer to Figures 1 to 3 The description of the relevant steps in the corresponding embodiments will not be repeated here.

[0098] Furthermore, if the module / unit integrated in the electronic device 1 is implemented in the form of a software functional unit and sold or used as an independent product, it can be stored in a computer-readable storage medium. The computer-readable storage medium can be volatile or non-volatile. For example, the computer-readable medium can include: any entity or system that can carry the computer program code, a recording medium, a USB flash drive, a mobile hard disk, a magnetic disk, an optical disk, a computer memory, and a read-only memory (ROM).

[0099] The present invention also provides a computer-readable storage medium, which stores a computer program. When the computer program is executed by a processor of an electronic device, it can achieve: receiving an anti-corrosion and anti-wear instruction, and preparing a coating spray based on the anti-corrosion and anti-wear instruction, obtaining an original polymer material group, and setting an original coating thickness, wherein the coating spray includes: an adhesion coating spray and a resistance coating spray, and the original polymer material is in the form of a rectangular plate; based on the original coating thickness, each original polymer material in the original polymer material group is sprayed with a coating spray to obtain a target polymer material group, wherein the surface of the target polymer material is covered with a coating, and the thickness of the coating is the original coating thickness; experimentally grouping the target polymer material group to obtain an anti-corrosion material group and an anti-wear material group; performing corrosion treatment on the anti-corrosion material group to obtain a material anti-corrosion rate group, wherein the number of material anti-corrosion rates in the material anti-corrosion rate group is the same as the number of anti-corrosion materials; performing friction treatment on the anti-wear material group to obtain a material wear rate group, wherein, The number of material wear rates in the material wear rate group is the same as the number of anti-wear materials; based on the material corrosion resistance rate group and the material wear rate group, anti-corrosion and anti-wear analysis is performed to obtain an anti-corrosion and wear factor; the original coating thickness and the anti-corrosion and wear factor are paired to obtain a thickness factor group, and the thickness factor group is added to the pre-constructed original thickness factor group set to obtain a target thickness factor group set; it is determined whether the anti-corrosion and wear factor is greater than a preset standard corrosion factor; if the anti-corrosion and wear factor is not greater than the standard corrosion factor, the original coating thickness is increased according to the target thickness factor group set to obtain a target coating thickness; the original coating thickness and the original thickness factor group set are respectively updated using the target coating thickness and the target thickness factor group set, and the step of spraying each original polymer material in the original polymer material group using a coating spray based on the original coating thickness is returned; if the anti-corrosion and wear factor is greater than the standard corrosion factor, the original coating thickness is recorded as the optimal coating thickness, and anti-corrosion and anti-wear based on polymer materials are completed based on the optimal coating thickness.

[0100] In the several embodiments provided by the present invention, it should be understood that the disclosed devices, systems and methods can be implemented in other ways. For example, the system embodiments described above are only illustrative, and actual implementation may have other division methods.

[0101] The modules described as separate components may or may not be physically separated, and the components shown as modules may or may not be physical units, that is, they may be located in one place or distributed on multiple network units. Some or all of the modules may be selected according to actual needs to achieve the purpose of the solution of this embodiment.

[0102] In addition, each functional module in each embodiment of the present invention may be integrated into one processing unit, each unit may exist physically separately, or two or more units may be integrated into one unit. The above-mentioned integrated unit may be implemented in the form of hardware or in the form of hardware plus software functional modules.

[0103] It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and that the present invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the present invention.

[0104] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for anti-corrosion and anti-wear based on high molecular polymer materials, characterized in that: The method comprises: receiving an anti-corrosion and anti-wear instruction, preparing a coating spray based on the anti-corrosion and anti-wear instruction, obtaining an original polymer material group, and setting an original coating thickness, wherein the coating spray comprises an adhesion coating spray and a resistance coating spray, and the original polymer material is in the form of a rectangular plate; based on the original coating thickness, spraying each original polymer material in the original polymer material group with the coating spray to obtain a target polymer material group, wherein the surface of the target polymer material is covered with a coating, and the thickness of the coating is the original coating thickness; experimentally grouping the target polymer material group to obtain An anti-corrosion material group and an anti-wear material group; performing corrosion treatment on the anti-corrosion material group to obtain a material anti-corrosion rate group, wherein the number of material anti-corrosion rates in the material anti-corrosion rate group is the same as the number of anti-corrosion materials; performing corrosion treatment on the anti-corrosion material group to obtain a material anti-corrosion rate group, comprising: setting the material environmental pH, and preparing an environmental salt solution based on the material environmental pH; extracting the anti-corrosion materials in the anti-corrosion material group in turn, and obtaining a control material of the anti-corrosion material, wherein the anti-corrosion material and the control material have the same mass and shape; soaking the anti-corrosion material and the control material in the environmental salt solution respectively, to obtain to the test anti-corrosion material and the test control material; at each corrosion time in the preset corrosion time group, respectively detect the test anti-corrosion quality and the test control quality of the test anti-corrosion material and the test control material to obtain the test anti-corrosion quality group and the test control quality group; according to the test anti-corrosion quality group and the test control quality group, perform material corrosion resistance analysis to obtain the material corrosion resistance rate; summarize the material corrosion resistance rate to obtain the material corrosion resistance rate group; the material corrosion resistance analysis according to the test anti-corrosion quality group and the test control quality group to obtain the material corrosion resistance rate includes: extracting the test anti-corrosion quality group in turn The anti-corrosion quality is tested, and the predecessor anti-corrosion quality of the test anti-corrosion quality is identified, wherein the predecessor anti-corrosion quality is the test anti-corrosion quality measured last time before the test anti-corrosion quality is measured; the current corrosion time and the predecessor corrosion time of the test anti-corrosion quality and the predecessor anti-corrosion quality are identified respectively, and the current control quality and the predecessor control quality are extracted from the test control quality group based on the current corrosion time and the predecessor corrosion time; the unit anti-corrosion rate is calculated according to the test anti-corrosion quality, the predecessor anti-corrosion quality, the current corrosion time, the predecessor corrosion time, the current control quality and the predecessor control quality, wherein the unit anti-corrosion rate is expressed as: ,in, Represents the unit corrosion resistance rate, Indicates the current control quality, Indicates the quality of the preceding control. Indicates the test anti-corrosion quality, Indicates the anti-corrosion quality of the previous order, Indicates the current corrosion duration. Indicates the duration of the preceding corrosion; Summarize the unit anti-corrosion rates to obtain a unit anti-corrosion rate set, calculate the average anti-corrosion rate of the unit anti-corrosion rate set, and record the average anti-corrosion rate as the material anti-corrosion rate; perform friction treatment on the anti-wear material group to obtain a material wear rate group, wherein the number of material wear rates in the material wear rate group is the same as the number of anti-wear materials; perform friction treatment on the anti-wear material group to obtain the material wear rate group, including: setting friction test parameters of a pre-constructed friction test device, wherein the friction test parameters include: friction time, friction load, friction frequency, friction speed and friction temperature, and the friction test device is a ball-disc friction and wear tester; extract anti-wear materials in the anti-wear material group in turn, start the friction test device based on the friction test parameters, and use the friction test device to rub the anti-wear material to obtain the wear material; measure the wear material volume of the wear material, and obtain the contact area between the friction test device and the anti-wear material, and calculate the material wear rate according to the wear material volume, contact area and preset original material volume, wherein the material wear rate is expressed as: ,in, represents the material wear rate, represents the original material volume, represents the volume of wear material, represents the friction load, Representing the contact area; summarizing the material wear rates to obtain a material wear rate group; performing anti-corrosion and anti-wear analysis based on the material anti-corrosion rate group and the material wear rate group to obtain an anti-corrosion and wear factor, wherein the anti-corrosion and wear factor refers to a numerical value used to represent the corrosion resistance and wear resistance of the target polymer material; performing anti-corrosion and anti-wear analysis based on the material anti-corrosion rate group and the material wear rate group to obtain the anti-corrosion and wear factor, including: setting an anti-corrosion weight factor and an anti-wear weight factor; calculating the anti-corrosion and wear factor according to the anti-corrosion weight factor, the anti-wear weight factor, the material anti-corrosion rate group and the material wear rate group using the following formula: , ,in, Represents the anti-corrosion factor, Indicates the number of material corrosion resistance rates in the material corrosion resistance rate group. Indicates the number of material wear rates in the material wear rate group, represents the anti-corrosion weight factor, represents the corrosion rate of the i-th material in the material corrosion rate group, represents the anti-wear weight factor, Represents the j-th material wear rate in the material wear rate group; pairs the original coating thickness and the anti-corrosion factor to obtain a thickness factor group, and adds the thickness factor group to the pre-constructed original thickness factor group set to obtain a target thickness factor group set, wherein the thickness factor group refers to an array consisting of the original coating thickness and the anti-corrosion factor; determines whether the anti-corrosion factor is greater than a preset standard corrosion factor, wherein the standard corrosion factor refers to an artificially set corrosion factor constant; if the anti-corrosion factor is not greater than the standard corrosion factor, then according to the target thickness factor group set, the original coating thickness is increased to obtain a target coating thickness, wherein the target coating thickness refers to the increased original coating thickness; the original coating thickness and the original thickness factor group set are respectively updated using the target coating thickness and the target thickness factor group set, and the step of spraying each original polymer material in the original polymer material group using a coating spray based on the original coating thickness is returned; if the anti-corrosion factor is greater than the standard corrosion factor, then the original coating thickness is recorded as the optimal coating thickness, and the anti-corrosion and anti-wear based on the polymer material is completed based on the optimal coating thickness.

2. The anti-corrosion and anti-wear method based on high molecular polymer materials according to claim 1, characterized in that: The method for preparing the coating spray comprises: obtaining raw materials for preparing the spray, wherein the raw materials for preparing the spray comprise: epoxy resin, deionized water, 3-aminopropyl triethoxysilane, nano-sized titanium dioxide particles, precipitated silica particles, phosphoric acid, silane coupling agent KH-570, methyl methacrylate and glycidyl methacrylate; adding the epoxy resin to deionized water to obtain an original resin mixture, and subjecting the original resin mixture to ultrasonic vibration and constant temperature stirring to obtain a dissolved resin mixture, wherein the ultrasonic vibration and constant temperature stirring are respectively performed by using an ultrasonic oscillator for ultrasonic vibration and using a constant temperature magnetic stirrer for constant temperature stirring; 3-aminopropyltriethoxysilane is added to the dissolved resin mixture to obtain an adhesion coating spray; the phosphoric acid and deionized water are mixed to obtain a base mixture, and nano-scale titanium dioxide particles and precipitated silica particles are added to the base mixture to obtain an original particle mixture, and the original particle mixture is subjected to ultrasonic oscillation treatment to obtain a uniform particle mixture; silane coupling agent KH-570 and methyl methacrylate are dropped into the uniform particle mixture to obtain an original resistance mixture, and the original resistance mixture is stirred at a constant temperature to obtain a uniform resistance mixture; the glycidyl methacrylate is added to the uniform resistance mixture to obtain a resistance coating spray.

3. The anti-corrosion and anti-wear method based on high molecular polymer materials as claimed in claim 2, characterized in that: The method of spraying each original polymer material in the original polymer material group with the coating spray to obtain the target polymer material group includes: setting the spraying height, the static curing time and the high-temperature curing time, and extracting the original polymer materials in the original polymer material group in sequence; based on the spraying height, using a pre-constructed spraying device to evenly spray the adhesion coating spray on the surface of the original polymer material to obtain a liquid film polymer material, and based on the static curing time, allowing the liquid film polymer material to stand at room temperature to obtain a preliminary cured material; using the resistant coating spray and the preliminary cured material to update the adhesion coating spray and the original polymer material respectively, and returning to the method of evenly spraying the adhesion coating spray on the original polymer material based on the spraying height using the pre-constructed spraying device The step of: curing the surface of the polymer material; based on the high-temperature curing time, and using the pre-acquired drying device, the preliminary cured material is subjected to high-temperature curing at a preset curing temperature to obtain a fully cured material; measuring the material coating thickness of the fully cured material, and judging whether the material coating thickness is less than the original coating thickness; if the material coating thickness is less than the original coating thickness, the original polymer material is updated with the fully cured material, and the step of returning to the spraying height-based, pre-constructed spraying device to uniformly spray the adhesion coating spray on the surface of the original polymer material; if the material coating thickness is not less than the original coating thickness, the fully cured material is recorded as the target polymer material, and the target polymer materials are summarized to obtain a target polymer material group.

4. The anti-corrosion and anti-wear method based on high molecular polymer materials as claimed in claim 3, characterized in that: The method of increasing the original coating thickness according to the target thickness factor set to obtain the target coating thickness includes: obtaining the target group number of the target thickness factor set, and determining whether the target group number is greater than the preset standard group number; if the target group number is not greater than the standard group number, increasing the original coating thickness according to the target group number and the standard group number to obtain the target coating thickness, wherein the target coating thickness is expressed as: ,in, represents the target coating thickness, Indicates the number of standard groups, Indicates the number of target groups, Represents the original coating thickness; if the target group number is greater than the standard group number, the original coating thickness is increased based on the target thickness factor set to obtain the target coating thickness.

5. The anti-corrosion and anti-wear method based on high molecular polymer materials according to claim 4, characterized in that: The method of increasing the original coating thickness based on the target thickness factor set to obtain the target coating thickness includes: extracting a historical coating thickness set and a historical corrosion factor set of the target thickness factor set, and calculating a factor variation coefficient set based on the historical coating thickness set and the historical corrosion factor set, wherein the factor variation coefficient set is expressed as: ,in, represents the set of factor variation coefficients, represents the u-th factor change coefficient in the factor change coefficient set, Indicates the first Historical corrosion factor, represents the u-th historical corrosion factor, The first Historical coating thickness, represents the uth historical coating thickness, represents the number of target groups; identifies the effective variation coefficient in the factor variation coefficient set, and calculates the target coating thickness according to the effective variation coefficient, the original coating thickness, the anti-corrosion factor and the standard corrosion factor, wherein the effective variation coefficient and the target coating thickness are respectively expressed as: , ,in, represents the effective coefficient of variation, Indicates the concentration of factor variation coefficient The coefficient of variation of the factor, represents the target coating thickness, Represents the standard corrosion factor.

6. An anti-corrosion and anti-wear system based on polymer materials, characterized in that: The system comprises: a coating spray preparation module, which is used to receive an anti-corrosion and anti-wear instruction, and prepare a coating spray based on the anti-corrosion and anti-wear instruction, obtain an original polymer material group, and set an original coating thickness, wherein the coating spray comprises: an adhesion coating spray and a resistance coating spray, and the original polymer material is in the form of a rectangular plate, and based on the original coating thickness, each original polymer material in the original polymer material group is sprayed with a coating spray to obtain a target polymer material group, wherein the surface of the target polymer material is covered with a coating, and the thickness of the coating is the original coating thickness; a corrosion and wear data acquisition module, which is used to collect the The target polymer material group is experimentally grouped to obtain an anti-corrosion material group and an anti-wear material group, and the anti-corrosion material group is subjected to corrosion treatment to obtain a material anti-corrosion rate group, wherein the number of material anti-corrosion rates in the material anti-corrosion rate group is the same as the number of anti-corrosion materials, and the anti-corrosion material group is subjected to corrosion treatment to obtain a material anti-corrosion rate group, including: setting the material environmental pH, and preparing an environmental salt solution based on the material environmental pH; extracting anti-corrosion materials in the anti-corrosion material group in turn, and obtaining a control material of the anti-corrosion material, wherein the anti-corrosion material and the control material have the same mass and the same shape; respectively immersing the anti-corrosion material and the control material in water. The method comprises the following steps: soaking the test anti-corrosion material in the environmental salt solution to obtain a test anti-corrosion material and a test control material; at each corrosion time in the preset corrosion time group, respectively detecting the test anti-corrosion quality and the test control quality of the test anti-corrosion material and the test control material to obtain a test anti-corrosion quality group and a test control quality group; performing a material corrosion resistance analysis based on the test anti-corrosion quality group and the test control quality group to obtain a material corrosion resistance rate; summarizing the material corrosion resistance rates to obtain a material corrosion resistance rate group; performing a material corrosion resistance analysis based on the test anti-corrosion quality group and the test control quality group to obtain a material corrosion resistance rate, including: in the test corrosion resistance quality group The test anti-corrosion quality is extracted in sequence, and the predecessor anti-corrosion quality of the test anti-corrosion quality is identified, wherein the predecessor anti-corrosion quality is the test anti-corrosion quality measured last time before the test anti-corrosion quality is measured; the current corrosion time and the predecessor corrosion time of the test anti-corrosion quality and the predecessor anti-corrosion quality are identified respectively, and the current control quality and the predecessor control quality are extracted from the test control quality group based on the current corrosion time and the predecessor corrosion time; the unit anti-corrosion rate is calculated according to the test anti-corrosion quality, the predecessor anti-corrosion quality, the current corrosion time, the predecessor corrosion time, the current control quality and the predecessor control quality, wherein the unit anti-corrosion rate is expressed as: ,in, Represents the unit corrosion resistance rate, Indicates the current control quality, Indicates the quality of the preceding control. Indicates the test anti-corrosion quality, Indicates the anti-corrosion quality of the previous order, Indicates the current corrosion duration. Indicates the duration of the preceding corrosion; Summarize the unit anti-corrosion rates to obtain a unit anti-corrosion rate set, calculate the average anti-corrosion rate of the unit anti-corrosion rate set, and record the average anti-corrosion rate as the material anti-corrosion rate, perform friction treatment on the anti-wear material group to obtain a material wear rate group, wherein the number of material wear rates in the material wear rate group is the same as the number of anti-wear materials, and perform friction treatment on the anti-wear material group to obtain the material wear rate group, including: setting friction test parameters of a pre-constructed friction test device, wherein the friction test parameters include: friction time, friction load, friction frequency, friction speed and friction temperature, and the friction test device is a ball-disc friction and wear tester; extract anti-wear materials in the anti-wear material group in turn, start the friction test device based on the friction test parameters, and use the friction test device to rub the anti-wear materials to obtain wear materials; measure the wear material volume of the wear material, and obtain the contact area between the friction test device and the anti-wear material, and calculate the material wear rate according to the wear material volume, contact area and preset original material volume, wherein the material wear rate is expressed as: ,in, represents the material wear rate, represents the original material volume, represents the volume of wear material, represents the friction load, Indicates the contact area; summarizes the material wear rate to obtain a material wear rate group; a target thickness calculation module is used to perform anti-corrosion and anti-wear analysis based on the material anti-corrosion rate group and the material wear rate group to obtain an anti-corrosion and wear factor, wherein the anti-corrosion and wear factor refers to a numerical value used to represent the corrosion and wear resistance of the target polymer material, and the anti-corrosion and anti-wear analysis based on the material anti-corrosion rate group and the material wear rate group to obtain the anti-corrosion and wear factor includes: setting an anti-corrosion weight factor and an anti-wear weight factor; according to the anti-corrosion weight factor, the anti-wear weight factor, the material anti-corrosion rate group and the material wear rate group, the anti-corrosion and wear factor is calculated using the following formula: , ,in, Represents the anti-corrosion factor, Indicates the number of material corrosion resistance rates in the material corrosion resistance rate group. Indicates the number of material wear rates in the material wear rate group, represents the anti-corrosion weight factor, represents the corrosion rate of the i-th material in the material corrosion rate group, represents the anti-wear weight factor, represents the j-th material wear rate in the material wear rate group; the original coating thickness and the anti-corrosion factor are paired to obtain a thickness factor group, and the thickness factor group is added to the pre-constructed original thickness factor group set to obtain a target thickness factor group set, wherein the thickness factor group refers to an array consisting of the original coating thickness and the anti-corrosion factor, and whether the anti-corrosion factor is greater than a preset standard corrosion factor is determined, wherein the standard corrosion factor refers to an artificially set corrosion factor constant, if the anti-corrosion factor is not greater than the standard corrosion factor, then the original coating thickness is increased according to the target thickness factor group set to obtain a target coating thickness, wherein the target coating thickness refers to the increased original coating thickness; an optimal thickness confirmation module is used to update the original coating thickness and the original thickness factor group set respectively using the target coating thickness and the target thickness factor group set, and return the step of spraying each original polymer material in the original polymer material group using a coating spray based on the original coating thickness, and if the anti-corrosion factor is greater than the standard corrosion factor, then the original coating thickness is recorded as the optimal coating thickness.

Citation Information

Patent Citations

  • Transformer oil tank assembly design method and system and storage medium

    CN118070562A

  • Gas turbine blade

    JP1994159003A